2010
DOI: 10.1002/app.33142
|View full text |Cite
|
Sign up to set email alerts
|

Relating scratch resistance to injection molding‐induced morphology of polypropylene

Abstract: ABSTRACT:The relationship between the scratch resistance and the injection molding-induced morphology of polypropylene (PP) was investigated. The crystal structure near the surface was controlled by the mold temperature and the doping of a nucleating agent (NA). Although aand b-NA were used to improve the scratch resistance of PP that was molded at a mold temperature of 40 C, both of the NAs only slightly affected the scratch resistance due to low crystallinity at the surface. When the mold temperature was inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Work by other authors already proved the influence of the injection molding process on the scratch resistance of PP samples. Kobayashi and Otsuki for example connects an increased scratch resistance with an increased tool temperature, whereas Chivatanasoontorn and Koji found increasing injection speed, i.e. shear rate, to cause increasing scratch resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Work by other authors already proved the influence of the injection molding process on the scratch resistance of PP samples. Kobayashi and Otsuki for example connects an increased scratch resistance with an increased tool temperature, whereas Chivatanasoontorn and Koji found increasing injection speed, i.e. shear rate, to cause increasing scratch resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Polypropylene (PP) has been widely used in automotive industry. The scratch behavior of PP has drawn much attention since the scratch can significantly affect its surface aesthetics . It has been found that crystallinity, additives, molecular weight, etc.…”
Section: Introductionmentioning
confidence: 99%